KEKUASAAN PRESIDEN DALAM PEMBERIAN GRASI MENURUT UUD 1945 - Untung Dwi Hananto (Faculty of Law, Universitas Diponegoro, 2013)
Abstract President has the power to grant an application for a gratie. That application must met with The Supreme Court recommendation. The Presidential Decision can be in the formation of giving or deniying gratie.The term for granting or rejecting gratie must be in the length of three months since The Supreme Court recommendation. The granting of gratie and amnesty are executive power, not yudicative power. It is executed outside the judicial process. This power is to execute prior or before the judicial process not to eliminated the judicial process. Keywords : Gratie and Amnesti Abstrak Presiden memberikan keputusan atas permohonan grasi setelah memperhatikan pertimbangan Mahkamah Agung. Keputusan Presiden dapat berupa pemberian atau penolakan grasi. Jangka waktu pemberian atau penolakan grasi paling lambat 3 (tiga) bulan terhitung sejak diterimanya pertimbangan Mahkamah Agung Pemberian grasi dan amnesti adalah kekuasaan eksekutif, bukan kekuasaan yustisial. Kekuasaan tersebut dilaksanakan di luar proses yustisial. Kekuasaan ini dilaksanakan sesudah atau sebelum proses yustisial, bukan meniadakan proses yustisial. Kata Kunci : Grasi dan Amnesti